Nucleic acid nanoassembly-enhanced RNA therapeutics and diagnosis - Mengnan Zhao; Rujing Wang; Kunmeng Yang; Yuhong Jiang; Yachen Peng; Yuke Li; Zhen Zhang; Jianxun Ding; Sanjun Shi (Elsevier, 2023)
RNAs are involved in the crucial processes of disease progression and have emerged as powerful therapeutic targets and diagnostic biomarkers. However, efficient delivery of therapeutic RNA to the targeted location and precise detection of RNA markers remains challenging. Recently, more and more attention has been paid to applying nucleic acid nanoassemblies in diagnosing and treating. Due to the flexibility and deformability of nucleic acids, the nanoassemblies could be fabricated with different shapes and structures. With hybridization, nucleic acid nanoassemblies, including DNA and RNA nanostructures, can be applied to enhance RNA therapeutics and diagnosis. This review briefly introduces the construction and properties of different nucleic acid nanoassemblies and their applications for RNA therapy and diagnosis and makes further prospects for their development.